Prioritizing regional agricultural R&D investments in Africa: incorporating R&D spillovers and economywide effects - Johnson, Michael E.; Benin, Samuel; Diao, Xinshen; You, Liangzhi (International Food Policy Research Institute, 2011)
To achieve the first of the United Nations' Millennium Development Goals (MDGs), halving poverty and hunger by 2015, African countries have set a target of 6 percent agricultural GDP growth. Whether, and to what extent, this target can be achieved depends a great deal on the rate at which agricultural productivity can be accelerated, given current low levels in most countries. Because many countries in Africa have small economies and limited capacities and resources for effective R&D, focusing on a regional agricultural R&D strategy can help fill these gaps and facilitate scale economies. While the need for regional cooperation in R&D is well known, as is evident from the efforts of organizations such as the Forum for Agriculture Research in Africa (FARA), the Association for Strengthening Agricultural Research in Eastern and Central Africa (ASARECA), and the West and Central African Council for Agricultural Research and Development (CORAF/WECARD), a key challenge is having empirically sound evidence and methods for setting regional R&D priorities that are also consistent with the resource constraints and development objectives of the individual countries.